PROGRAM OF SOCIO-PEDAGOGICAL PREVENTION OF ANXIETY IN ADOLESCENTS IN THE CONDITIONS OF A GENERAL EDUCATIONAL SCHOOL - Magauova, Akmaral; Kertayeva, Galiyabanu; Dukenbayeva, Zhanel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article discusses the problem of substantiating the need for social and pedagogical prevention of anxiety in adolescents in a general education school and the organization of the educational process, which takes into account the peculiarities of anxiety in adolescents. A theoretical analysis of the literature and the study of the experience of educational work in general education schools allow us to conclude that the educational process is not sufficiently focused on the prevention of anxiety among adolescents among the middle level.The aim of the research is to develop and approbate a program of social and pedagogical prevention of anxiety in adolescents in a comprehensive school. The structure of the study is based on the requirements of modern higher education, which is based on the professional competencies of the educational paradigm. The main results of the study allow us to determine the effectiveness of the developed program for the prevention of anxiety in adolescents. Based on the results of the analysis of the theory, the structure and methods of a social-pedagogical program for the prevention of anxiety will be revealed, using the example of the use of the methodology "Personal school of anxiety by J. Taylor" (1953). The question of the research is how to develop a program of social and pedagogical prevention of anxiety in adolescents, which will be systemic, holistic, personal and active in nature and will be effective.